Impact Analysis of Russia’s Invasion of Ukraine on McDonald’s Operations in Russia - Dea Harmonita Ernst; Rizal Budi Santoso (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
McDonald’s is a highly popular multinational fast-food company that has operated in Russia for over 30 years. However, following the Russia-Ukraine invasion, its operations became unstable, leading the company to decide to close its outlets and sell its business to local entrepreneurs. This decision was prompted by various factors, including community activism and international sanctions. Moreover, the company incurred significant financial losses due to the closure of its stores, totaling $1.4 billion. This study also investigates how McDonald’s adapted to the risk of brand dilution by rebranding as Vkusno i Tocha to protect its global image. Using a descriptive qualitative method with an analytical framework based on Nash Equilibrium theory and conflict theory. The result of this study; finds that McDonald’s acknowledged the need to withdraw from the Russian market due to the invasion and aimed to mitigate further negative impacts.